2014
DOI: 10.1093/heapro/dau028
|View full text |Cite
|
Sign up to set email alerts
|

Framing of Influenza A (H1N1) pandemic in a Singaporean newspaper

Abstract: SUMMARYThis study seeks to understand how public health messages provided by the government in Singapore during an Influenza A (H1N1) pandemic were framed by the news media for the public. News articles were analyzed to explore how the global pandemic was framed as a local event, providing a unique exploration of the dynamic involving public health communication, news media and the state. Thematic analysis (n ¼ 309) included the government-issued press releases disseminating public health information about H1N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…Their study revealed that the news coverage focused more on H1N1 information updates and prevention than on other frames. In another one of their articles [ 20 ], four additional news themes were found— imported disease , war/battle metaphors , social responsibility and lockdown policy . Shih, Wijaya and Brossard [ 21 ] focused on news coverage about the mad cow disease, West Nile virus and avian flu from the New York Times by examining six frames— consequence , uncertainty , action , reassurance , conflict , new evidence .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study revealed that the news coverage focused more on H1N1 information updates and prevention than on other frames. In another one of their articles [ 20 ], four additional news themes were found— imported disease , war/battle metaphors , social responsibility and lockdown policy . Shih, Wijaya and Brossard [ 21 ] focused on news coverage about the mad cow disease, West Nile virus and avian flu from the New York Times by examining six frames— consequence , uncertainty , action , reassurance , conflict , new evidence .…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an authoritarian context, the press takes a leading role in conveying public health messages (Schwartz, 2012;Basnyat and Lee, 2015). In Singapore, (Deurenberg-Yap et al, 2005) revealed that there was high trust in the state and its institutions in the management and knowledge transfers of the epidemic, despite limited knowledge about control measures and the SARS virus itself by Singaporeans.…”
Section: The Press In Singaporementioning
confidence: 99%
“…According to the recent report on "framing of Influenza A (H1N1) pandemic in a Singaporean newspaper," Basnyat and Lee concluded that "news coverage during the H1N1 pandemic reflected how the newspaper framed and mediated the information flow, amplified a positive tone for the government response." 3 In fact, the role of newspaper and other mass media during new emerging disease pandemic is an interesting issue. It is of no doubt that, the mass media can bring both positive and negative attitude.…”
Section: To the Editormentioning
confidence: 99%